Composição químico-bromatológica e digestibilidade da dieta e desempenho produtivo de ovinos em capim-tanzânia sob três frequências de desfolhação e dois resíduos pós-pastejo - Valente, Bruno Stefano Miranda (2007)
The research was carried out at the advanced field of the Forage Teaching and Research Nucleus - NEEF/DZ/CCA/UFC (www.neef.ufc.br), located at Curu Valley Experimental Farm - FEVC/CCA/UFC, in Pentecoste/CE. The aim of this research was to evaluate the nutritional value of the simulated diet and the productive performance of sheep grazing in Panicum maximum cv. Tanzania under three defoliation frequencies, determined by the interception of the photosynthetically active radiation in canopy (PAR) of 85, 95 and 97 % and two post-grazing residues, determined by the residual leaf area index (LAI) of 1.0 and 1.8. A completely randomized design in factorial arrangement 3x2 (three defoliation frequencies and two residues after graze), with four repetitions for the variable of the grass (poles) and around the six (sheep) for the variable related to the animals, having still cycles of graze as measured repeated in the time. 90 sheep without defined breeding standard had been used (SPRD), averaging an initial live weight of 20.0 kg were used. 6 sheep were allocated to each treatment, resulting in 36 tester sheep. The others 44 sheep were used as put-and-taken animal, to keep the canopy as established by the end of the grazing period. For determination of the chemical composition assay, digestibility and an in situ dry matter degradation trial, a simulation of grazing in 1st and 4th days was carried out. An animal performance assay was conducted, beyond the determination of the carrying capacity in each grazing system. The defoliation frequency reduction diminished the diet nutritional value and the sheep performance. The highest animal live weight productivity toward the year was obtained in the 85% defoliation frequency on both post-grazing residues and at the intermediate defoliation frequency only at the residual leaf area index of 1.0. So, one xi recommends to adopt a defoliation frequency of tanzania grass up to 95% of photosynthetically active radiation interception, with a residual LAI of 1.0 to obtain a compromise between the objectives of animal production and forage quality maintenance in the long term.